'One Stop Centres' and state accountability for sexual violence against women: comparing service integration models in Kenya and South Africa - Lekakeny, Ruth Nekura (Department of Public Law, 2021)
There is increasing recognition that sexual violence victims have multiple and complex needs, requiring the joint intervention of multiple sectors to generate a more effective response. As such, multi-sector collaborations that integrate health, legal and psychosocial support services are acknowledged as a best practice intervention. Despite the dearth of evidence on how such integration approaches operate in resource-constrained settings, they continue to be established and scaled up in parts of Africa. Using a qualitative case-study approach, this thesis seeks to understand how integration approaches in Kenya and South Africa contribute to the fulfilment of the human rights obligations of states to prevent and effectively respond to sexual violence against women. I use interview data to compare Kenya’s Gender Based Violence Recovery Centres and South Africa’s Thuthuzela Care Centres across rural, peri-urban and urban contexts. The thesis moves away from current analysis approaches, which assess integration models based on separate, sector-specific outcome indicators, such as health or criminal justice system outcomes. I use a feminist human rights perspective, based on the state’s responsibility to exercise due diligence in prevention, protection, prosecution, punishment and provision of adequate redress. This perspective facilitates the centrality of victims’ needs and rights in assessing service integration models, while foregrounding the need for state accountability to establish sustainable and effective sexual violence interventions. I argue that multisector approaches that integrate sexual violence services are complex networks, which produce different service orientations, shaped by the interactions of collaborating partners, amidst fundamental systemic and structural flaws. In the governance of collaboration systems, different service orientations emerge as stakeholders within networks, wield their resources, mentalities, methods and institutions to produce certain outcomes as priority over others. Consequently, as competing sector-specific mandates and ideologies are prioritised, multi-sector approaches can eclipse and de-centre the needs and rights of sexual violence victims.